TRANSFORMASI ORGANISASI BIROKRASI, PENGGUNAAN TEKNOLOGI INFORMASI DAN PROFESIONALISME TERHADAP KINERJA DAN BERDAMPAK PADA PRESTASI KERJA - Abu Hasan Asy'ari; Juhari; Afrizal; Wargianto; Panca Tuah Tuha (Universitas Sarjanawiyata Tamansiswa, 2024)
The research aims to analyze the influence of bureaucratic organizational transformation, the use of information technology, and professionalism on employee performance which has an impact on work performance at the Regional Office of the Ministry of Religion of Bangka Belitung Province. The method was quantitative with a questionnaire distributed to 114 respondents, data processing with SmartPLS 4.0 software. The results of the study showed: The transformation of bureaucratic organization, information technology and professionalism affects employee performance partially and simultaneously. Organizational transformation of bureaucracy and professionalism has an effect on work performance while the use of information technology has no effect on work performance; employee performance affects work performance; bureaucratic organizational transformation, the use of information technology, professionalism and employee performance affect work performance; Bureaucratic organizational transformation and the use of information technology through employee performance mediation have an effect on work performance while professionalism through employee performance mediation has no effect on work performance